Characterization of Chlamydia DNA by restriction endonuclease cleavage. - Peterson, E M (1983)
The DNA from six serovars of Chlamydia trachomatis, lymphogranuloma venereum (LGV) I, LGV II, LGV III, B, C, and D, and from Chlamydia psittaci was extracted, treated with restriction endonuclease enzymes, and run on agarose gels. By using this technique, the DNA of C. trachomatis could be clearly differentiated from C. psittaci DNA. A comparison of the DNA from the different serovars of C. trachomatis revealed similar patterns with and without detectable differences. LGV I, LGV II, LGV III, B, and C revealed no differences when treated with BamHI, HaeIII, XbaI, and XhoI. LGV III DNA, when cleaved with EcoRI and HhaI, had a major band migrating faster than the other two LGV serovars. Serovar D had a different pattern from all other strains tested when cleaved with BamHI, EcoRI, HhaI, HincI, and XhoI. When treated with SacI and HgaI, LGV II displayed a unique band not seen in the other LGV serovars. Differences in strains could be attributed to both chromosomal and plasmid DNA.